Perancangan Alat Bantu Pemindahan Part Crossmember untuk Mencegah Cedera MSDs dengan Metode NBM dan REBA di PT. GKD - Adinatra, Yudistira; Arifin, Jauhari (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
GKD is an automotive manufacturing company. One of the products from PT. GKD is Crossmember which weighs 34 kg. During the part checking process at the Quality Control station, there is a manual handling activity from the bottom of the floor to the pallet carried out by the production operator. The position of taking the part does not match the operator's body posture so the operator takes the part while bending over. Based on interviews and distributing NBM questionnaires to operators, it was found that operators suffered musculoskeletal injuries to the hips, back, arms, shoulders and legs. This research was conducted to reduce activities that have the potential to cause musculoskeletal injuries to operators, by using the NBM (Nordic Body Map) questionnaire method to analyze ergonomic risks and analyzing work postures using the Rapid Entire Body Assessment (REBA) method before the proposed assistive equipment. As well as calculating the operator's anthropometric dimensions to obtain suitable dimensions for the tool. Keywords: Musculoskeletal disorders; manual handling; NBM; REBA